2000
DOI: 10.1210/endo.141.8.7623
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Expression of a Rat Renin Transcript Lacking the Coding Sequence for the Prefragment and Its Stimulation by Myocardial Infarction*

Abstract: An alternative transcript of the rat renin gene was recently characterized in the adrenal gland, in addition to the known messenger RNA (mRNA) coding for preprorenin. In the alternative transcript, exon 1 is replaced by exon 1A, a domain originating in intron 1. The reading frame of this mRNA, termed exon 1A-renin transcript, codes for a truncated prorenin that presumably remains intracellular, in contrast to preprorenin, which is targeted to the secretory pathway by its prefragment. We here demonstrate the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 35 publications
2
16
1
Order By: Relevance
“…In contrast we consistently detected renin-b in human hearts and thus conclude that this transcript is not brain-specific as previously suggested. These results are in agreement with our data in the rat [11].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In contrast we consistently detected renin-b in human hearts and thus conclude that this transcript is not brain-specific as previously suggested. These results are in agreement with our data in the rat [11].…”
Section: Discussionsupporting
confidence: 94%
“…In the rat we observed a specific upregulation of renin-b expression under various ischemia-related conditions. Thus, glucose depletion in cardiac cells in vitro and ligation of left coronary arteries in rats in vivo increased transcript levels of renin-b but not of secretory renin [11]. Therefore, we suggested that renin-b transcript levels are increased also in human heart diseases.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations